Ensino de astronomia através de disciplina eletivas - uma experiência no ensino médio de Araguaína-TO - CARVALHO, Nayara Alves de Oliveira de (Universidade Federal do Tocantins, 2023)
Astronomy teaching is of fundamental importance for understanding the universe we live in. Although recommended in the official documents that govern national education, little is seen about this area of knowledge within the classrooms. The present work is the result of a research with students and professor of an elective discipline of Astronomy offered in basic education in the city of Araguaína. The work aims to analyze the students' relationship with astronomy, and the knowledge obtained through the discipline. In addition, it aims to investigate the main difficulties encountered by the teacher when teaching such subjects. This work aimed to analyze the teaching of astronomy that has been offered through an elective course in a state school in the public basic education network in the city of Araguaína